Iridociliary adenocarcinoma with oncocytic change in a dog - OKAWAUCHI, Mitsuteru (J Vet Med Sci, 2016)
An intraocular mass lesion was found in the left eyeball in a spayed female Pembroke Welsh Corgi dog. The surgically resected left eyeball was pathologically examined. Histologically, the mass lesion consisted of proliferation of the atypical cuboidal or columnar epithelial cells, arranging in papillary, tubular or solid form. In addition, some neoplastic cells showed oncocytic change characterized as large oval cells with numerous eosinophilic intracytoplasmic granules. Cytoplasm of the oncocytic cells showed dark blue granules by phosphotungstic acid-hematoxylin stain. Immunohistochemically, the oncocytic cells were intensely positive for cytochrome C. Based on these findings, the ocular mass was diagnosed as iridociliary adenocarcinoma with oncocytic change. The findings indicate that the oncocytic changes of the neoplastic epithelial cells might be caused by mitochondrial accumulation.